Optimal Multipath Conveyance with Improved Survivability for WSN's In Challenging Location - Chen, Joy Iong Zong (Journal of ISMAC, 2020)
The sensor networks with the capability of conveying information's through the wireless medium in many circumstances are affected by the inner energy and the exterior atmospheric changes as the sensors are employed in the areas that are beyond human reach and left uncared. Since routing procedure seems as the main source of energy utilization in these types of networks formulated by the sensors and as the prevailing routing procedures considers the parametric optimization from the network perception alone eluding the atmospheric influences over the network from the exterior sources, makes the sensors obtuse to the sudden unexpected changes in the atmosphere. So this leads to failure in conveyance of information's due to the failure in the routing and the fading of the path established. To manage such circumstance effectively the paper formulates a multi path conveyance with improved survivability for wireless-sensor-networks. The method takes into consideration the residual energy, depth and the dynamic changes in the atmosphere. The developed routing evades the information from passing over the hazardous area and forms a reliable conveyance by creating an atmosphere based on the monitoring competencies of the sensor network. The formulate method is experimentally evaluated using the network simulator-2 to acquire the vital enhancements in the life expectancy of the network framed and the delivery rate of the packets.
Keywords: Wireless sensor networks; Challenging Environment; Routing; Survivability; Life expectancy; Packet Delivery Ratio